Adherence of deaf individuals to health services: Exploring the use of communication apps (Research, Society and Development, 2025)
Objectives: To present the communication barriers of deaf people in health services and identify tools (applications) used to reduce the difficulties encountered. Methodology: This is a cross-sectional study, carried out from September to October 2024 through interviews with deaf individuals. The interview questions were divided into three main areas: Sample characterization; Health services; and Use of applications. Results and Discussion: Twenty-six deaf people of both sexes, aged between 18 and 41 years, were interviewed, most of whom were profoundly deaf. The need to facilitate communication among deaf people was highlighted, since 11.54% avoid communicating with hearing people and 30.77% use only Libras. The vast majority of deaf people go to health services accompanied and use the SUS. Six communication applications were presented, with the ICOM application standing out. Conclusion: When analyzing the data, it was observed that the main barriers for deaf people are the difficulty of understanding the professional who treats them and the need for a companion. In addition, it was shown that the frustration and anguish of not being understood can be one of the factors that reduce the adherence of deaf people to health services. The deaf people highlighted some applications that can help; however, the need for health professionals to learn Libras, or the development of new tools that are more appropriate, should not be ruled out.